2006
DOI: 10.2501/s0021849906060041
|View full text |Cite
|
Sign up to set email alerts
|

How to Capture the Heart? Reviewing 20 Years of Emotion Measurement in Advertising

Abstract: In the latest decades, emotions have become an important research topic in all behavioral sciences, and not the least in advertising. Yet, advertising literature on how to measure emotions is not straightforward. The major aim of this article is to give an update on the different methods used for measuring emotions in advertising and to discuss their validity and applicability. We further draw conclusions on the relation between emotions and traditional measures of advertising effectiveness. We finally formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
177
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(185 citation statements)
references
References 49 publications
2
177
0
6
Order By: Relevance
“…This study has demonstrated relevance of the emotional context on TVC effectiveness measured by the four indicators which are traditionally used in marketing research: Ad recall, Aad, Ab and PI (Poels & Dewitte, 2006). To the best of our knowledge, this is the first experimental study in which Ad recognition has been assessed by the reaction time, in which TVC effectiveness has been assessed by use of a completely novel TVC, and in which the emotional context has been manipulated by standardized stimuli from the IAPS (Lang et al, 2008) and the IADS (Bradley & Lang, 1999) databases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has demonstrated relevance of the emotional context on TVC effectiveness measured by the four indicators which are traditionally used in marketing research: Ad recall, Aad, Ab and PI (Poels & Dewitte, 2006). To the best of our knowledge, this is the first experimental study in which Ad recognition has been assessed by the reaction time, in which TVC effectiveness has been assessed by use of a completely novel TVC, and in which the emotional context has been manipulated by standardized stimuli from the IAPS (Lang et al, 2008) and the IADS (Bradley & Lang, 1999) databases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that contents preceding advertising can induce positive or negative emotions, which primarily affect the attitude toward the ad (Coulter, 1998;De Pelsmacker et al, 2010). Furthermore, a positive or a negative attitude toward the ad can affect the attitude toward the brand and the purchase intent (Coulter, 1998;Mackenzie, Lutz, & Belch, 1986;Mehta, 2000;Poels & Dewitte, 2006). The emotional context of TVC can be the program in which TVC is presented, or other TVCs in the same commercial break.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, reported responses can be biased because they rely on the respondents' ability and willingness to report their feelings. Furthermore, (especially long) item-based methods have been criticised not only for being generally burdensome and time-consuming (Curren et al, 1995), but also for requiring cognitive processing which may distort the original feelings (Poels & Dewitte, 2006). These limitations are particularly relevant when affect is assessed in naturalistic settings, such as before or after human-product or social interaction in the context of use.…”
Section: Verbal Self-report Measuresmentioning
confidence: 99%
“…In addition, the use of emotional scales which often contains a long list of emotion adjectives might cause respondent fatigue. Moreover some of respondents have difficulties in to expressing their feeling because they are not always aware of them and/or certain pressure from social bias (Poels and Dewitte, 2006).…”
Section: Introductionmentioning
confidence: 99%